Therapeutical properties of apigenin: a review on the experimental evidence and basic mechanisms - Zarina Mushtaq; Nabeelah Bibi Sadeer; Muzzamal Hussain; Mahwish; Suliman A. Alsagaby; Muhammad Imran; Tamseela Mumtaz; Maryam Umar; Ambreen Tauseef; Waleed Al Abdulmonem; Tabussam Tufail; Entessar Al Jbawi; et al. (International Journal of Food Properties)
Apigenin (4,’5,7-trihydroxyflavone) is one of the most studied flavonoids with low toxicity and abundantly present phenolic compound in the plant kingdom. The main sources of apigenin are fruits, vegetables, nuts, herbs, honey, and plant-based drinks like tea. Numerous plants produce apigenin as a secondary metabolite and its intake is strongly related to its anti-inflammatory propensities. The purpose of present review was to wade through the literature on the anti-inflammatory mechanisms of this metabolite in various diseases and summarize the key objectives as they appear. Existing literature reported that apigenin is a promising candidate in managing a panoply of inflammatory-related diseases including cancer, diabetes, obesity, depression, insomnia, infection, and respiratory, cardiovascular, hepatoprotective, neurodegenerative, and skin diseases. Studies showed that apigenin significantly decreases the secretion of various proinflammatory cytokines specifically tumor necrosis factor (TNF)-α, IL-1β, IL-6, and IL-10. Moreover, apigenin effectively blocks the nitric oxide-mediated cyclooxygenase-2 expression and monocyte attachment and Prostaglandin by lowering iNOS and COX-2 in both microglial and macrophage mouse cells. Apigenin can slow the course of nonalcoholic fatty liver disease (NAFLD) in vivo by reducing high fat diet (HFD)-induced deposition of lipids and oxidative stress. It also controlled redox imbalances, suppress neuronal death and showed memory enhancement/learning skills and a reduction of fibrillar amyloid deposits with lowered insoluble Aβ concentrations in vivo. Taken together, it can be argued that apigenin can wane inflammation and thus offers a promising future in slowing down the development of chronic diseases and associated complications.